Adapting an equity-focused implementation process framework with a focus on ethnic health inequities in the Aotearoa New Zealand context - Papillon Gustafson; Michelle Lambert; Karen Bartholomew; Mihi Ratima; Yasmin Abdul Aziz; Lisa Kremer; Adam Fusheini; Peter Carswell; Rachel Brown; Patricia Priest; Sue Crengle (International Journal for Equity in Health, 2024)
Abstract Background Health intervention implementation in Aotearoa New Zealand (NZ), as in many countries globally, usually varies by ethnicity. Māori (the Indigenous peoples of Aotearoa) and Pacific peoples are less likely to receive interventions than other ethnic groups, despite experiencing persistent health inequities. This study aimed to develop an equity-focused implementation framework, appropriate for the Aotearoa NZ context, to support the planning and delivery of equitable implementation pathways for health interventions, with the intention of achieving equitable outcomes for Māori, as well as people originating from the Pacific Islands. Methods A scoping review of the literature to identify existing equity-focused implementation theories, models and frameworks was undertaken. One of these, the Equity-based framework for Implementation Research (EquIR), was selected for adaptation. The adaptation process was undertaken in collaboration with the project’s Māori and consumer advisory groups and informed by the expertise of local health equity researchers and stakeholders, as well as the international implementation science literature. Results The adapted framework’s foundation is the principles of Te Tiriti o Waitangi (the written agreement between Māori rangatira (chiefs) and the British Crown), and its focus is whānau (extended family)-centred implementation that meets the health and wellbeing aspirations, priorities and needs of whānau. The implementation pathway comprises four main steps: implementation planning, pathway design, monitoring, and outcomes and evaluation, all with an equity focus. The pathway is underpinned by the core constructs of equitable implementation in Aotearoa NZ: collaborative design, anti-racism, Māori and priority population expertise, cultural safety and values-based. Additionally, the contextual factors impacting implementation, i.e. the social, economic, commercial and political determinants of health, are included. Conclusions The framework presented in this study is the first equity-focused process-type implementation framework to be adapted for the Aotearoa NZ context. This framework is intended to support and facilitate equity-focused implementation research and health intervention implementation by mainstream health services.